KEANEKARAGAMAN JENIS TEGAKAN PENYUSUN TEMBAWANG DI DESA RAJA KECAMATAN NGABANG KABUPATEN LANDAK - Wahyuni, Ayu; Dewantara, Iswan; Ardian, Hafiz (Universitas Tanjungpura, 2014)
The research aims to know the diversity types of stands compilers Tembawang, and research carried out on the Tembawang in the Village King, subdistrict of Ngabang Regency landak. The method used is a combination method is a modification of the method line by line method terraced and placed in a purposive sampling. Results of the analysis of the date shows that the stands are found as many as 34 types for all levels of growth. Of the 34 types of stands are included: Acids, Bandong, Cempedak, Durian, Empirical, Ensubal, Entepong, Jambu bol, Jambu hutan, Kandis, Kandaria, Rubber, Kelitak, Kepayang landak, Coffee, Langsat, Mangosteen, Leban, Medang, Mentawak, Meramun, Pangsik, Peluntan, Pengan, Petai, Pulai pipit, Rambai, Rambutan, Rembawan, Rengas, Tengkawang, Terap and Tuba. The result showed that the level of INP all types have the greatest number on Tembawang I and Tembawang II, namely Cempedak (Artocarpus champeden) the family Moraceae, while in the Tembawang III and IV Tembawang the family of Euphorbiaceae, namely Rubber (Hevea braziliensis). Overall dominance index value (C) at all locations of research including low, because it has not yet reached the dominance of the highest index value (C = 1). The results of data analysis index values diversity in all kinds of Tembawang on the level low (< H 1). At the level of the stake and the pillar, Tembawang I have a kind of low diversity values and on Tembawang II to Tembawang IV diversity of its kind is abundant (1 ? H ? 3). At the level of the tree, Tembawang I and Tembawang IV has a value type of diversity is low (< 1 H), whereas in Tembawang II and Tembawang III has a value of the type being abundant (1 ? H ? 3). Keywords : Diversity, Stands, Tembawang, Village King